Investigating lower secondary school students’ geometric argumentation structure using Toulmin model - Ramandani, M. Rizky; Hartono, Yusuf; Hiltrimartin, Cecil; Aisyah, Nyimas (Jurnal Elemen, 2024)
Geometric argumentation has an important role in solving mathematical problems in geometric material, so students must have this ability. Each student has different thoughts, including when stating arguments. Each student's arguments will vary and be at different levels. This study aims to determine the levels of lower secondary school students' geometric argumentation. This research was conducted in a lower secondary school involving 20 ninth-grade students. Students participating in this study were asked to work on geometry problems related to proof. Through the proofs carried out, the argumentation structure owned by students is visible. The structures of argumentation given by the students were then analysed using Toulmin's model of argumentation.  The components of the Toulmin model used consist of claim, data, warrant, and backing.  The results of the analysis of the proof prepared by the students stated that some of the students have been able to reach a high level of geometric argumentation and can compile a series of proofs. But not a few of them also have difficulty compiling the proof, have difficulty providing the components of the Toulmin model, and make some mistakes. Errors made by students include symbol writing errors, calculation errors, and others.